Extraction of lipids from post-hydrolysis spent coffee grounds for biodiesel production with hexane as solvent: Kinetic and equilibrium data. (September 2020) - Go, Alchris Woo; Pham, Thi Yen Nhu; Ju, Yi-Hsu; Agapay, Ramelito C.; Angkawijaya, Artik Elisa; Quijote, Kristelle L.
Abstract: Spent coffee grounds (SCG), an agro-industrial residue produced after brewing of coffee beans contains appreciable amounts of lipids (~16 wt%). One way of valorizing SCG is to subject it to dilute acid hydrolysis for the production of sugar-rich hydrolysate and lipid-dense post-hydrolysis residue. The post-hydrolysis spent coffee grounds (PHSCG) contains substantial amounts of lipids (~26 wt%), making it necessary to gather lipid extraction kinetics and equilibrium data for process and equipment design. The effects of solvent-to-solid ratio (4–20 mL g −1 ) and temperature (30–60 °C) on the kinetics and equilibrium of lipid extraction from PHSCG using hexane as solvent was investigated. To appropriately describe the lipid extraction system, various kinetic models were fitted, with multi-step models best representing the extraction process (R 2  ≥ 0.99). Regardless of extraction temperature and SSR, washing step equilibrium is reached at a very short extraction time (<10 min) and over 90% of the lipids can be extracted in at least 1 h. Extraction of lipids from PHSCG required less amount of solvent to extract and recover the same amount of lipids present in SCG saving up to 40% of the solvent required for lipid extraction from SCG. Highlights: Post-hydrolysis spent coffee grounds (PHSCG) contain more lipids than native SCG. Lipids recovered from PHSCG are suitable as feedstock for biodiesel production. At least 80% of the available lipids could be extracted in less than 10 min. Up to 40% less solvent is required to recover lipids from Post-hydrolysis SCG.